2021
DOI: 10.1039/d1sc04571g
|View full text |Cite
|
Sign up to set email alerts
|

A core–brush 3D DNA nanostructure: the next generation of DNA nanomachine for ultrasensitive sensing and imaging of intracellular microRNA with rapid kinetics

Abstract: This study designed a highly loaded and integrated core–brush 3D DNA nanomachine for miRNA imaging and sensing, which easily solves the major technical challenges of traditional Au-based 3D nanomachines: low loading capacity and low executive efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…As we can see from Figure 9, the corresponding ECL response also increased significantly when the number of MCF-7 cells increased, but the ECL intensity did not increase obviously with the growing number of Hela cells, which indicated that the expression of miRNA-21 in MCF-7 cells was higher than in Hela cells. Those results showed agreement with previous reports, 29,30 indicating that this constructed biosensor could be used to detect the expression of miRAN-21 in cancer cells.…”
Section: ■ Results and Discussionsupporting
confidence: 93%
“…As we can see from Figure 9, the corresponding ECL response also increased significantly when the number of MCF-7 cells increased, but the ECL intensity did not increase obviously with the growing number of Hela cells, which indicated that the expression of miRNA-21 in MCF-7 cells was higher than in Hela cells. Those results showed agreement with previous reports, 29,30 indicating that this constructed biosensor could be used to detect the expression of miRAN-21 in cancer cells.…”
Section: ■ Results and Discussionsupporting
confidence: 93%
“…It is well known that DNA nanostructures have become versatile and indispensable biological tools for constructing biomarker detection strategies by virtue of their precise nucleobase sequence control, ideal chemical modification functions, outstanding addressing ability, and excellent recognition properties. In the fields of molecular biology and medical diagnostics, many smart nanodevices, such as DNA gears, DNA tweezers, DNA tetrahedrons, and DNA walkers, have been designed to perform specific recognition, transmission, and sensing functions. It is worth mentioning that reconfigurable DNA nanostructures could achieve addressable conformational changes in response to external stimuli such as fuel, temperature, light, and pH, providing a new idea for realizing the dynamic and continuous monitoring of biomarkers. Unfortunately, these methods required the introduction of additional substances or a change in experimental conditions, which might make the reaction system complex and uncontrollable, reduce the anti-interference performance, and eventually lead to false-positive results.…”
Section: Introductionmentioning
confidence: 99%
“…Metal-assisted DNA catalyst (DNAzyme) is a class of special single-stranded DNA and can catalyze the cleavage of specific RNA substrates through the high ion-dependent enzymatic property (such as Mg 2+ , Mn 2+ , Pb 2+ , Zn 2+ ). DNAzymes have emerged as a powerful tool for biomolecular detection that take the advantages of enzyme-free cleavage, facile synthesis, remarkable stability, and programmability. For instance, Chu et al have reported a lipofectamine-transfected target-assisted self-cleavage DNAzyme probes for the imaging of multiple miRNA, and an exonuclease III-initiated integrated DNAzyme amplifier has also been developed for intracellular miRNA imaging by delivering through cation liposomes . Furthermore, to promote the amplification efficiency of individual DNAzymes, some tandem isothermal DNA amplification circuits were also developed, including the hybridization chain reaction (HCR)-DNAzyme circuit, the catalyzed hairpin assembly (CHA)-DNAzyme circuit, and the CHA-HCR-DNAzyme multiple cascade circuit, which added versatility and programmability for amplified miRNA assay.…”
Section: Introductionmentioning
confidence: 99%